2017
DOI: 10.1038/s41598-017-01768-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA markers for identification of Beluga and Sterlet sturgeons and their interspecific Bester hybrid

Abstract: Sturgeons (Acipenseriformes) are among the most endangered species in the world due to fragmentation and destruction of their natural habitats and to overexploitation, mainly for highly priced caviar. This has led to the development of sturgeon culture, originally for reintroduction, but more recently for caviar production. In both cases, accurate species identification is essential. We report a new tool for accurate identification of Huso huso and Acipenser ruthenus based on nuclear DNA markers. We employed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
2
27
1
1
Order By: Relevance
“…The positive result for a single Amur sturgeon and, conversely, lack of amplification in three Siberian and eight Russian sturgeons is probably due to genetic admixture, as also observed by Boscari et al . The marker, combined with others already available (Table ), will contribute to enforcing controls against fraud and illegal trade of sturgeon products. Moreover, the ability to detect hybridization with Russian or Siberian sturgeon is relevant for ex situ conservation programs given that hybridization is considered an immediate genetic threat to endangered populations …”
Section: Developed Primer Pair and Validation Tests Performed In 12 Ssupporting
confidence: 70%
See 1 more Smart Citation
“…The positive result for a single Amur sturgeon and, conversely, lack of amplification in three Siberian and eight Russian sturgeons is probably due to genetic admixture, as also observed by Boscari et al . The marker, combined with others already available (Table ), will contribute to enforcing controls against fraud and illegal trade of sturgeon products. Moreover, the ability to detect hybridization with Russian or Siberian sturgeon is relevant for ex situ conservation programs given that hybridization is considered an immediate genetic threat to endangered populations …”
Section: Developed Primer Pair and Validation Tests Performed In 12 Ssupporting
confidence: 70%
“…Sixteen samples each of sterlet, Siberian sturgeon and beluga were analyzed by ddRAD sequencing described previously (Appendix ). At positions 33 and 34 of a 110‐bp ddRAD fragment, an AG variant was observed in all 655 reads of the Siberian sturgeon, whereas a CA variant was observed in all 410 reads of the sterlet and in all 505 reads of the beluga (Fig.…”
Section: Developed Primer Pair and Validation Tests Performed In 12 Smentioning
confidence: 99%
“…The larvae of most sturgeon species can be unambiguously identified only by appropriate molecular markers 45 . To uncover, whether NT-fish contains genome of Russian sturgeon donor, we accommodated recently developed nuclear DNA markers 46 . The results of molecular genotyping clearly showed that NT-fish contains only sterlet genome.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were tested by sterlet positive primer pair 247_AR + 247_uni and subsequently by sterlet negative primer pair 247_ARn + 247_uni as described in Havelka, et al . 46 . If a sample contains only sterlet DNA, the 247 bp fragment is amplified only by sterlet positive primer pair.…”
Section: Methodsmentioning
confidence: 99%
“…Above methods have difficulties with mass application in aquaculture and can have a high error (the first two methods) or can traumatize fish (the last four methods). Furthermore, a sturgeon sex gene has not been found, unlike most fish species (Fopp‐Bayat, ; Keyvanshokooh & Gharaei, ; Khodaparast, Keyvanshokooh, Pourkazemi, Hosseini, Keyvanshokooh, Pourkazemi, Hosseini, & Zolgharnein, ; Vizziano‐Cantonnet, Di Landro, & Lasalle, ); however, a study in this area are still under way (Burcea et al, ; Havelka, Fujimoto, Hagihara, Adachi, Fujimoto, Hagihara, Adachi, & Arai, ; Vizziano‐Cantonnet et al, ; Vizziano‐Cantonnet, Lasalle, DiLandro, Klopp, & Genthon, ). Currently, the ultrasound diagnostics is the most successful method of early sturgeon sex determination (Chebanov & Galich, ; Memiş et al, ; Webb et al, ) and can determine the sex starting from 2 years for Sterlet sturgeon ( Acipenser ruthenus ), from 2–3 years for Siberian ( A. baerii ) and Russian ( A. gueldenstaedtii ) sturgeons, from 3–4 years for White sturgeon ( A. transmontanus ) and from 4–5 years in Beluga ( Huso huso ) (Chebanov & Galich, ).…”
Section: Introductionmentioning
confidence: 99%